(untitled) (Journal of Health, Population and Nutrition, 2009)
The degree of binding of a drug to plasma proteins has a marked effect on its distribution, elimination, and pharmacological effect since only the unbound fraction is available for distribution into extra-vascular space. The protein-binding of atenolol was measured by equilibrium dialysis in the bovine serum albumin (BSA). Free atenolol concentration was increased due to addition of arsenic which reduced the binding of the compounds to BSA. During concurrent administration, arsenic displaced atenolol from its high-affinity binding Site I, and free concentration of atenolol increased from 4.286±0.629% and 5.953±0.605% to 82.153±1.924% and 85.486±1.158% in absence and presence of Site I probe respectively. Thus, it can be suggested that arsenic displaced atenolol from its binding site resulting in an increase of the free atenolol concentration in plasma. Key words: Arsenic; Atenolol; Bovine serum albumin; Drug interactions; Plasma protein-binding doi: 10.3329/jhpn.v27i1.3315 J Health Popul Nutr 2009 Feb;27(1):20-30